Acute postoperative pain relief, by intraperitoneal application of local anesthetics, during laparoscopic cholecystectomy - Ljiljana Gvozdenović (Journal of Health Sciences, 2011)
Introduction: Intraperitoneal administration of local anesthetic in combination with an opioid, for the relief of postoperative pain, has already been reported after laparoscopic cholecystectomy. This study aimed to assess the analgesic effect of the intraperitoneal administration of bupivacaine and morphine, in patients undergoing laparoscopic cholecystectomy. Methods: 90 patients (30 patients in each group) were included in a double blind, randomized manner. At the end of laparoscopic cholecystectomy, the patients were intraperitoneally treated with 30 ml of: physiological saline (Group 1) or 0.25% bupivacaine (Group 2) or 0.25% bupivacaine + 2 mg morphine (Group 3). Patient’s postoperative pain was evaluated using a visual analogue scale and a verbal rating score. The postoperative analgesic requirement was assessed by the total dose of Ketorolak, administered by intravenous or intramuscular route. Pain, vital signs, supplemental analgesics consumption and side effects were recorded for all patients for 12h. Results: There were no difference between the three groups, regarding pain scores (et rest and coughing) during the study, except in the fi rst 6 h, when scores were lower for patients receiving intraperitoneal bipuvacaine + morphine (p<0.05). Conclusions: In the patients undergoing laparoscopic cholecystectomy, the intraperitoneal administration of bupivacaine + morphine, reduced the analgesic requirements during the fi rst 6 postoperative hours compared with the control groups. The combination of intraperitoneal bupivacaine 0.25% and morphine was more effective for treatment of pain after laparoscopic cholecystectomy.